Systemic responses in a tolerant olive (Olea europaea L.) cultivar upon root colonization by the vascular pathogen Verticillium dahliae - Gómez-Lama Cabanás, Carmen (Front Microbiol, 2015)
Verticillium wilt of olive (VWO) is caused by the vascular pathogen Verticillium dahliae. One of the best VWO management measures is the use of tolerant cultivars; however, our knowledge on VWO tolerance/resistance genetics is very limited. A transcriptomic analysis was conducted to (i) identify systemic defense responses induced/repressed in aerial tissues of the tolerant cultivar Frantoio upon root colonization by V. dahliae, and (ii) determine the expression pattern of selected defense genes in olive cultivars showing differential susceptibility to VWO. Two suppression subtractive hybridization cDNA libraries, enriched in up-regulated (FU) and down-regulated (FD) genes respectively, were generated from “Frantoio” aerial tissues. Results showed that broad systemic transcriptomic changes are taking place during V. dahliae-“Frantoio” interaction. A total of 585 FU and 381 FD unigenes were identified, many of them involved in defense response to (a)biotic stresses. Selected genes were then used to validate libraries and evaluate their temporal expression pattern in “Frantoio.” Four defense genes were analyzed in cultivars Changlot Real (tolerant) and Picual (susceptible). An association between GRAS1 and DRR2 gene expression patterns and susceptibility to VWO was observed, suggesting that these transcripts could be further evaluated as markers of the tolerance level of olive cultivars to V. dahliae.